(untitled) (Revista Innova Educación, 2021)
The dynamics of science and technology are the primary elements of the sustainable development of society in all areas. In the educational context, they have given rise to new forms of flexible, open and free or low-cost learning, such as MOOC (Massive Open Online Courses) that, supported by emerging technologies, have a social effect and contribute to the democratization of knowledge. In this sense, the main objective of this work is to identify the implications (limitations and scope) of MOOCs for the development of an inclusive education supported by emerging technologies and their impact on society, taking into account the main factors that generate it and develop, from the STS (Science, Technology and Society) vision, through the application of historical-logical, analysis and synthesis methods and finally generalization-abstraction, taking primary and secondary bibliographic sources as important, with the purpose that the institutions educational institutions incorporate MOOC as an alternative for permanent training and updating of knowledge that the knowledge society demands so much.